The effects of consumer esports videogame engagement on consumption behaviors - Abbasi, A.Z. (Emerald Group Holdings Ltd., 2021)
Purpose: This study aims to propose a model for predicting consumersâ esports videogame engagement on their ensuing consumption behaviors, which remains nebulous to date. Design/methodology/approach: After approaching esports consumers in different gaming zones in Pakistan, this paper collected data from 364 videogame-based esports consumers. This paper deployed SmartPLS 3.2.8 software to perform the partial least squares-structural equation modeling-based analyzes. Findings: The structural model results show that consumersâ affective and behavioral esports videogame engagement positively affects their consumption behavior, including heightened community engagement, purchase intent, coproduction, word-of-mouth and new player recruitment. However, while consumersâ cognitive esports engagement was found to positively impact community engagement, new player recruitment and coproduction, it failed to predict consumersâ esports-related purchase intent or word-of-mouth behaviors. Practical implications: The findings reveal that a strategic focus on consumersâ esports game engagement will enable practitioners to nurture desirable consumer behaviors, including enhanced purchase intent, coproduction, word-of-mouth and new player recruitment behaviors, thus warranting consumer engagementâs strategic value as a key esports gaming metric. Originality/value: Empirical research into the role of consumersâ esports videogame engagement on their ensuing consumption behaviors remains scant to date. Based on this gap, this study offers a timely contribution by exploring and validating a model that gauges the effect of consumersâ cognitive, emotional and behavioral esports videogame engagement on their community engagement, purchase intention, coproduction, word-of-mouth and new player recruitment. It, thus, offers important insight into the rapidly advancing field of digital esports games. Â© 2020, Emerald Publishing Limited.